Conceptualizing the clinical decision-making process in managing temporomandibular disorders:A qualitative study - Ilgunas, A.; Lövgren, A.; Fjellman-Wiklund, A.; Häggman-Henrikson, B.; Karlsson Wirebring, L.; Lobbezoo, F.; Visscher, C.M.; Durham, J. (European Journal of Oral Sciences, 2021)
© 2021 The Authors. European Journal of Oral Sciences published by John Wiley & Sons Ltd on behalf of Scandinavian Division of the International Association for Dental ResearchManagement of patients with temporomandibular disorders (TMD) appears to be more challenging than for other dental conditions. This study aimed to explore the decision-making process in TMD management, and thereby to conceptualize the decision-making process in dentistry. Individual semi-structured interviews were conducted during 2018 and 2019 with a purposive sample of 22 general dental practitioners from the Public Dental Healthcare Services and private practices in the Region of Västerbotten, Northern Sweden. The interviews were analysed using the Grounded Theory approach of Charmaz. Data analysis resulted in the core category ‘Combining own competence and others’ expectations in the desire to do the right thing’. The dentists showed interest in and a desire to apply professional knowledge, but also reflected on challenges and complexity in the decision-making process for TMD. The challenges were primarily related to organisational factors and lack of self-confidence. This identifies a need for re-organisation of daily clinical management in dentistry, and a need for more postgraduate training to improve self-confidence. The complexity of the decision-making process for TMD makes the study findings applicable in other dental situations.